Laparoscopic management of second trimester ruptured cornual heterotopic pregnancy with subsequent live birth delivery: A case report and literature review - Yi-Ling Li; Fei-Chi Chuang; Kuo-Chung Lan (Elsevier, 2023)
Objective: Heterotopic pregnancy (HP) is the coexistence of extra- and intrauterine gestation implantation sites. A rare case of a second-trimester ruptured cornual HP (CHP) treated with laparoscopic cornual resection with the primary repair is presented. Risk factors, clinical presentations, treatments, and outcomes of CHPs are also reviewed. Case report: A 35-year-old pregnant woman with CHP presented with lower abdominal pain with hemoperitoneum and her hemoglobin level dropped. Laparoscopic management of a ruptured HP was performed, leaving the surplus intrauterine fetus intact. She delivered a 2360 g male infant via cesarean section at 34 weeks' gestation due to preterm premature rupture of membranes. We found a well-healed wound over the left uterine cornua during the cesarean section. Conclusion: Ruptured CHP is a rare but life-threatening complication of an obstetric emergency. Although the pregnant uterus becomes congested and fragile, using reliable laparoscopic energy devices and barbed sutures, successful treatment is feasible.